2018
DOI: 10.1021/acs.jctc.8b00872
|View full text |Cite
|
Sign up to set email alerts
|

Designing Long-Range Charge Delocalization from First-Principles

Abstract: Efficient electronic communication over long distances is a desirable property of molecular wires. Charge delocalization in mixed-valence (MV) compounds where two redox centers are linked by a molecular bridge is a particularly well-controlled instance of such electronic communication, thus lending itself to comparisons between theory and experiment. We study how to achieve and control longrange charge delocalization in cationic organic MV systems by means of Kohn−Sham density functional theory (DFT) and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…The BLYP35 functional is a compromise hybrid, “35” meaning that it incorporates 35 % of exact exchange, this percentage being adjusted to describe properly the state of localization/delocalization . Recent uses of this protocol appear promising, in particular to design molecular wires with long‐range charge delocalization …”
Section: Theoretical Descriptionsmentioning
confidence: 99%
“…The BLYP35 functional is a compromise hybrid, “35” meaning that it incorporates 35 % of exact exchange, this percentage being adjusted to describe properly the state of localization/delocalization . Recent uses of this protocol appear promising, in particular to design molecular wires with long‐range charge delocalization …”
Section: Theoretical Descriptionsmentioning
confidence: 99%
“…In our previous studies on organic mixed-valence systems, the ratio between the local charges on the donor and acceptor moieties connected by a bridge served as a measure for the degree of charge localization, where complete charge delocalization would be expressed by a ratio of one, whereas a ratio of zero would indicate a fully localized charge on one redox centre. 48 Since here, the redox centers are replaced by non-redox-active anchoring groups, we define the degree of charge delocalization r deloc by relating the smallest possible subregion on which a suitably chosen large percentage of spin density is located to that percentage,…”
Section: Assessment Of Charge Delocalization 21 Definition Of Chargementioning
confidence: 99%
“…58 In a previous study on first-principles approaches, we validated different computational protocols based on Kohn-Sham density-functional theory (KS-DFT) regarding their capability of describing length-dependent charge localization in comparison with experiments for organic mixed-valence systems. 48 This type of donor-bridge-acceptor systems has the advantage of representing atomistically better-defined model systems than molecular junctions, while still being closely related to them as the electron transfer properties as expressed in their Robin-Day class are also length-dependent. 59,60 We found that, in contrast to other DFT protocols, a combination of the B1LYP hybrid functional with 35% Hartree-Fock exchange (BLYP35) and a polarizable continuum model (PCM), previously proposed by the group of Kaupp, [44][45][46] works well in this case.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations